2017
DOI: 10.1111/papr.12544
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study Comparing Platelet‐Rich Plasma and Local Anesthetic (LA)/Corticosteroid in Intra‐Articular Injection for the Treatment of Lumbar Facet Joint Syndrome

Abstract: Both autologous PRP and LA/corticosteroid for intra-articular injection are effective, easy, and safe enough in the treatment of lumbar facet joint syndrome. However, autologous PRP is a superior treatment option for longer duration efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
89
0
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(98 citation statements)
references
References 46 publications
4
89
0
5
Order By: Relevance
“…However, for group A, they increased over time. It was hence concluded that autologous PRP is a superior treatment option for longer duration efficacy [27]. This study addressed the previous two studies' lack of control group; however, it was limited by the small number of patients.…”
Section: Intra Facet and Ligament Injectionsmentioning
confidence: 95%
See 1 more Smart Citation
“…However, for group A, they increased over time. It was hence concluded that autologous PRP is a superior treatment option for longer duration efficacy [27]. This study addressed the previous two studies' lack of control group; however, it was limited by the small number of patients.…”
Section: Intra Facet and Ligament Injectionsmentioning
confidence: 95%
“…In 2017, a prospective comparative study randomized 46 patients into group A (intra-articular PRP) and group B (intra-articular local anesthetic and corticosteroid) [27]. Pain outcomes were measured using VAS, RMQ, ODI, and modified MacNab criteria.…”
Section: Intra Facet and Ligament Injectionsmentioning
confidence: 99%
“…В последнее время для улучшения результатов лечения рекомендуют внутрисуставное введение аутологической плазмы, обогащенной тромбоцитами (Platelet Rich Plasma Therapy, PRP) [43,44]. J. Wu и соавт.…”
Section: клиническая картинаunclassified
“…В обеих группах в послеоперационном периоде демонстрируется статистически достоверное (p<0,01) снижение интенсивности боли по шкалам Освестри, ВАШ и Роланда-Морриса. При этом в группе PRP результаты были достоверно лучше (p<0,05), чем в группе, получавшей глюкокортикостероиды [44].…”
Section: клиническая картинаunclassified
“…9 The limitations of currently available treatment modalities have sparked recent interest in potential alternative treatments for facet joint pain, although published data are currently sparse. 7,10 A potential alternative treatment for patients with insufficient response to conventional treatments is magnetic resonance imagingeguided focused ultrasound (MRgFUS). 7 Magnetic resonance imagingeguided focused ultrasound is a modality that utilizes a phased array transducer integrated within the magnetic resonance imaging (MRI) scanner to focus numerous high-energy ultrasound waves on a small focal spot in the body.…”
mentioning
confidence: 99%